Identifying and supporting reflection in pre-service teacher education: a rubric fit for purpose - Ellison, Maria (Linguarum Arena, 2021)
It is widely accepted that reflection and reflective practices are necessary components of teacher education programmes. However, these are not always explored or even fully understood by the very people who are expected to reflect – the student-teachers themselves. Support for these practices is therefore required so that students may understand what reflection is and helped to become reflective practitioners. This article describes the construction and use of a rubric to identify and support reflection in pre-service foreign language teacher education. It begins by reviewing key literature on reflection before moving on to a study of types of reflection and conceptual frameworks in the literature. Four types of reflection were identified and attributed labels: Type 0. Descriptive/behavioural; Type 1. Descriptive/analytical; Type 2. Dialogic/interpretative; and Type 3. Critical/transformatory. These were then used to construct the rubric which incorporated a matrix of five categories: discourse; rationale; level of inquiry; orientation to self; and views of teaching. Examples of how the rubric has been used to both capture and support reflection are provided. It is not a stand-alone tool, but one which is situated within a reflective practice model of teacher education which requires reflexive teacher educators, tools and practices which provide opportunities for reflection. It is flexible enough to allow teacher educators (and students) to identify types of reflection in spoken or written accounts, which may help when self-assessing, giving feedback, and supporting the momentum of reflection during a course or practicum.